A CALCULATION OF COST OF QUALITY WITH ACTIVITY BASED COSTING METHOD TO MAINTAIN QUALITY BETWEEN PRODUCTION PROCESSES - Purwanggono, Bambang; Valentinus, Rizalt (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2019)
ABSTRACT Quality is an image of a company. PT Berkat Manunggal Jaya is a company that its primary activity is to assemble the generator units. This company wants to improve its quality in its production processes. The Initial stage is to determine the amount of quality cost since it hasn’t been measured yet, especially in the production processes. This is because there are several cost categories that are within the company but the company still has not been able to measure them, which include the cost of diesel fuel for repeated inspection and the amount of diesel fuel that was carried when generators are delivered to the customers. The measuring method of this quality cost is using the Cost of Quality (COQ) model which details of the cost categories are based on Activity Based Costing (ABC) method. This method is suitable because it uses direct costs’ account, for instance, the use of materials as well as indirect costs as corporate overhead costs. The detail work instructions for the inspection of the production process between departments are provided based on existing procedures in the company. This is done to reduce the unacceptable product-in-progress when the production process is in operation. After calculating and put in all the activities into the four categories of Cost of Quality, the total Cost of Quality compared with the prices of sold unit from every generator set type are 1.77% for 680 KVA type open, 1.74% for 1300 KVA first type silent, 1.74% for 1300 KVA second type silent, 2.86% for 680 KVA type silent, 1.28% for 1300 KVA first type open, 1.27% for 1300 KVA second type open, 1.13% for 1740 KVA first type open, 1.13% for 1740 KVA second type open. The recommended solution for the reduction of Cost of Quality is to modify the procedure inspection flow in the company to reduce failure cost, especially in the final inspection costs (repeated test load processes).